Stimulasi Tumbuh Kembang Bayi Melalui Pijat Bayi - Desmariyenti Desmariyenti; Nurul Hidayah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Rokania, 2024)
A crucial period in a child's development is the toddler years, as this is the period during which basic growth influences and determines subsequent growth and development. For a child to achieve optimal growth, more intensive care is required, including continuous touch and stimulation, one of which is infant massage. Infant massage is beneficial for increasing a baby's appetite and weight. This action also strengthens the bond between parent and child, and provides a positive foundation for the baby's emotional and physical growth. The activity was held at the Sempena Negeri Pekanbaru Midwifery Academy and was attended by 30 mothers and their babies. The aim of this activity was to help parents, especially mothers, improve the growth and development of their babies through infant massage. The community service activity was carried out face-to-face using lectures and demonstrations, followed by a demonstration of infant massage by the mother. The activity went smoothly and the participants followed the socialization well and were able to perform baby massage on their children.